Techniques for formation of umbu-cajazeira seedlings by cuttings (Research, Society and Development, 2021)
The umbu-cajazeira still needs studies that can subsidize the propagator and those interested in disseminating clones of this culture in the agricultural environment, as it is a fruitful with a low percentage of viable seeds the and cuttings are an alternative for the production of cloned seedlings. Thus, the objective was to evaluate the use of rooting inducers and mini-greenhouses in the formation of cloned umbu-cajazeira seedlings by cutting. The experiment was carried out at the Embrapa Experimental Field, in Pacajus, Ceará, Brazil, in a nursery with a 50% sombrite®. A completely casualized design was used with six treatments, in a factorial scheme (3x2): rooting inducers Sela Gel®, Radimax® and without inducer, with and without mini-greenhouses, with four replications of ten cuttings/plot. The planting was in 6 L polyethylene pots, filled with a substrate composed of vermiculite, carnauba bagana, coconut powder and carbonized rice husks (2:1:1:1 v/v). The irrigation was carried out by sub-irrigation carried out twice a week, with half of the cuttings remained in mini-greenhouses for 44 days out of a total of 80 days of the experimental period. The cuttings treated with Sela Gel® differed significantly from the others, for all evaluated variables, presenting 51.25% of rooting, 30% of seedlings suitable for planting and an average of 29.50 leaflets per seedling. The cuttings treated with Radimax® showed a low percentage of rooting (22.50%) and, also, seedlings suitable for planting (7.50%). The use of mini-greenhouses favored greater callus formation in the cuttings.